2018
DOI: 10.3390/geosciences8120460
|View full text |Cite
|
Sign up to set email alerts
|

Local Variability of CO2 Partial Pressure in a Mid-Latitude Mesotidal Estuarine System (Tagus Estuary, Portugal)

Abstract: Estuaries play a crucial role in regional carbon cycling. Until now, accurate estimations of the impact of environmental variables on estuarine air–water CO2 fluxes have been mostly characterized by a low spatial-temporal sampling resolution. This study reports on the variations of CO2 partial pressure (pCO2) and related environmental parameters, at both tidal and seasonal temporal scales, in the surface seawater of a station located in the lower section of the Tagus estuary, Portugal. The study was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…The phase inversion observed in November and April (Figure 5), which occurred every year, was the consequence of the opposite SST seasonality between the CWM and the OWM (lower SST in summer in OWM and lower SST in winter in CWM). The influence of tides on pCO 2 dynamics is prominent in estuarine ecosystems (De la Paz et al, 2007;Bozec et al, 2012;Oliveira et al, 2018), but has also been observed in various continental shelves of the world ocean (DeGrandpre et al, 1998;Hofmann et al, 2011;Horwitz et al, 2019). Several studies have reported the impact of the tidal cycle on pCO 2 over various European continental shelf provinces, for example in the nWEC (Litt et al, 2010), in the Bay of Brest (Bozec et al, 2011) or in the Cadiz Bay (Ribas-Ribas et al, 2011.…”
Section: Short-scale Variability Of the Co 2 System In Coastal Swecmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase inversion observed in November and April (Figure 5), which occurred every year, was the consequence of the opposite SST seasonality between the CWM and the OWM (lower SST in summer in OWM and lower SST in winter in CWM). The influence of tides on pCO 2 dynamics is prominent in estuarine ecosystems (De la Paz et al, 2007;Bozec et al, 2012;Oliveira et al, 2018), but has also been observed in various continental shelves of the world ocean (DeGrandpre et al, 1998;Hofmann et al, 2011;Horwitz et al, 2019). Several studies have reported the impact of the tidal cycle on pCO 2 over various European continental shelf provinces, for example in the nWEC (Litt et al, 2010), in the Bay of Brest (Bozec et al, 2011) or in the Cadiz Bay (Ribas-Ribas et al, 2011.…”
Section: Short-scale Variability Of the Co 2 System In Coastal Swecmentioning
confidence: 99%
“…The shallower depth in the CMW favors light penetration, which can result in higher pelagic production (when nutrients are not depleted) compared to the deeper OWM. The role of benthic production processes on CO 2 variations is also important in proximal shallow areas (Hammond et al, 1999;Cai et al, 2000;Forja et al, 2004;Waldbusser and Salisbury, 2014;Oliveira et al, 2018). The low δpCO 2 non−therm associated to CWM during the productive period might include both higher pelagic and benthic production, with a predominance of the latter.…”
Section: Seasonal and Interannual Control Of Pco 2 In Coastal Swecmentioning
confidence: 99%
“…For the latter, the relatively deep water column and the limited amount of light reaching the seafloor might limit the contribution of the benthic compartment to the pelagic signal observed at the surface. Conversely, in the two shallow nearshore ecosystems, the benthic compartment may exert a strong control on the carbonate signal with high OM production/remineralization and/or CaCO 3 dissolution/precipitation characteristic of benthic communities in various coastal environments (Hammond et al, 1999;Cai et al, 2000;Forja et al, 2004;Martin et al, 2007;Waldbusser and Salisbury, 2014;Oliveira et al, 2018). These two nearshore stations were characterized by different benthic communities with maerl (coralline red algae) beds in the bay of Brest (e.g., Martin et al, 2007;Longphuirt et al, 2007;Lejart and Hily, 2011) and seagrass and macroalgae beds at SOMLIT-pier (Ouisse et al, 2011;Bordeyne et al, 2017).…”
Section: Comparison Between Ecosystems Of the Processes Controlling The Carbonate Systemmentioning
confidence: 99%